Understanding pandemic resilience: a mixed-methods exploration of burdens, resources, and determinants of good or poor well-being among Austrian psychotherapists - Schaffler, Yvonne; Bauer, Monika; Schein, Barbara; Jesser, Andrea; Probst, Thomas; Pieh, Christoph; Humer, Elke (Frontiers in Public Health, 2023)
Introduction The COVID-19 pandemic has exacerbated the mental health burden on the general population, resulting in increased demands on mental healthcare professionals, including psychotherapists. This cross-sectional study assessed the challenges and resources encountered by 513 psychotherapists based on an online survey conducted between April and May 2022. Methods Qualitative methods content analysis of written reports was employed to investigate the emerging challenges and sources of support during the pandemic. A comparative analysis of burdens, resources, sociodemographic factors and daily physical activity was conducted to discern patterns of good and poor well-being. Results The predominant burden identified was mental health-related issues, followed by global crises and government-imposed restrictions to mitigate virus transmission. Essential resources encompassed social connections, mindfulness, work satisfaction, and internal processes. Notably, psychotherapists demonstrating good well-being were older, more physically active, had a lower proportion of females, were employed in private practices rather than in institutionalized settings, had more years of professional experience and treated more patients weekly than their counterparts with poor well-being. Furthermore, they exhibited greater optimism, health focus, and satisfaction with their coping methods. Discussion These findings can help develop support systems, policies, and educational programs to better support mental health professionals during global crises and offer strategies for individual practitioners to maintain their well-being.